2021
DOI: 10.1088/1757-899x/1025/1/012009
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of slope stability analysis of Manganese slag stabilized soil to an ordinary soil

Abstract: Slopes are required in the construction of Highways, Railways, Earthen dams, canal banks, levees and at many other locations. The construction of embankment over the ground is not possible in a vertical way. The Soil can be piled up with slope only. The cost of earthwork is minimum if the slopes are steepest but the Steeper slopes are not safe as per stability conditions because it may fail in shear. The only force acting on the piled earth is gravity force. This gravitational force produces shear in the soil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Due to the large amount of active substances in MS, crushed and ground MS not only has a microaggregate filling effect on the cement but, also, can increase the hydration process [ 20 , 21 ]. In this way, the pore structure inside the concrete is improved, thus increasing the mechanical strength of cement concrete [ 22 ]. Maurilio et al have reported that the addition of MS decreased the porosity of cement concrete cured for 28 days, thus increasing the corresponding compressive strength at a rate of 0–42.1%.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the large amount of active substances in MS, crushed and ground MS not only has a microaggregate filling effect on the cement but, also, can increase the hydration process [ 20 , 21 ]. In this way, the pore structure inside the concrete is improved, thus increasing the mechanical strength of cement concrete [ 22 ]. Maurilio et al have reported that the addition of MS decreased the porosity of cement concrete cured for 28 days, thus increasing the corresponding compressive strength at a rate of 0–42.1%.…”
Section: Introductionmentioning
confidence: 99%